Manifestation of Old Arabic Culture in the Palestinian Folkloric Song and Mourning Poem: The Hair as an Example - Abdel khaleq Issa (My University, 2011)
This study deals with the relationship between old Arabic heritage and the Palestinian folkloric song and mourning poem in an attempt to uphold Palestinian culture and preserve its identity against the Israeli occupation’s attempts to sever this artery. I was eager to gather songs and mourning poems from the generation that used to chant them on occasions. I also surveyed samples of old poems and old common customs and sought the links between them and the Palestinian folkloric literature. I found that standard literature meets folkloric literature in dealing with small particulars such as the relationships between hair and the snake, hair and trees, hair and the water well, and hair and strength.